Impact of Teacher’s Pupil’s Class Relationship on Academics in Selected Schools of Bubare Town Council Rubanda District. - Amanya, Apollo (Kabale University, 2024)
This study explores the effect of teacher-pupil relationships on academic performance in selected schools within Bubare Town Council, Rubanda District. The objectives include examining the quality and nature of teacher-student interactions, assessing academic performance in relation to these relationships, and identifying factors that influence the dynamics between teachers and students. By using both qualitative and quantitative approaches, the research aims to understand how positive and negative relationships impact student engagement, motivation, and overall academic outcomes. Previous studies have established that strong teacher-student relationships are associated with improved academic performance (Hamre & Pianta, 2001; Roorda et al., 2011). The findings seek to provide insights into the importance of nurturing positive teacher-pupil relationships to boost educational success in schools within Bubare Town Council. The study underscores the need for teacher training programs that focus on relationship-building and communication skills, in line with recommendations from the National Education Association (2018), to foster supportive learning environments that promote academic achievement.